2020
DOI: 10.1016/j.cognition.2020.104426
|View full text |Cite
|
Sign up to set email alerts
|

Decision making in slow and rapid reaching: Sacrificing success to minimize effort

Abstract: Current studies on visuomotor decision making come to inconsistent conclusions regarding the optimality with which these decisions are made. When executing rapid reaching movements under uncertainty, humans tend to automatically select optimal movement paths that take into account the position of all potential targets (spatial averaging). In contrast, humans rarely employ optimal strategies when making decisions on whether to pursue two action goals simultaneously or prioritise one goal over another. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 56 publications
5
15
1
2
Order By: Relevance
“…If such a cognitive bias is at work, it could be a strong impediment to strategy optimization in situations with insufficient time to execute the targeted action. Importantly, the same tendency has been consistently observed in our previous studies 27 and in other recent studies 26,32 , necessitating the identification of its causes.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…If such a cognitive bias is at work, it could be a strong impediment to strategy optimization in situations with insufficient time to execute the targeted action. Importantly, the same tendency has been consistently observed in our previous studies 27 and in other recent studies 26,32 , necessitating the identification of its causes.…”
Section: Discussionsupporting
confidence: 86%
“…In this case, an important decision about the strategy for two potential targets is whether to focus on one target (i.e., a predetermined strategy) or to take both targets into account (i.e., a choice-reaction strategy). Previous studies confirmed that humans prefer a choice-reaction strategy even in situations with severe spatiotemporal constraints to sufficiently accomplish a task 26,27 . A similar bias may exist in the selection of strategies when encountering asymmetric time constraints in the go-before-you-know task.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…3A). This resulted in more initial and final decision errors during interception, supporting recent evidence that decision-making is impaired when the movement required is more demanding to perform (Hesse et al, 2020; Reynaud et al, 2020). The dorsal and ventral streams are driven predominantly by magnocellular and parvocellular inputs, respectively, and axons of parvocellular cells have slower conduction velocity than magnocellular cells (Maunsell et al, 1999).…”
Section: Discussionsupporting
confidence: 82%
“…Ao observarem os indivíduos como Homo economicus, os pesquisadores (e.g. Hesse, Kangur, & Hunt, 2020;Zeelenberg & Dijk, 1997), que estudam as teorias econômicas do processo de decisão, defendem que o esforço percebido diminui ou neutraliza o valor da recompensa e, assim, pode causar aversão à tarefa. Como elucidam Amirudin e Gin ( 2019), no contexto de compras de supermercado, quanto maior o esforço percebido em termos de deslocamento e tempo empenhado, maiores as chances de buscar meios para evitar realizar as compras.…”
Section: Esforço Percebidounclassified